Reference Standards for Software Evaluation - Michaelis, J.; Wellek, S.; Willems, J. L. (Methods of Information in Medicine, 1990)
The field of automated ECG analysis was one of the earliest topics in Medical Informatics and may be regarded as a model both for computer-assisted medical diagnosis and for evaluating medical diagnostic programs. The CSE project has set reference standards of two kinds: In a broad sense, a standard how to perform a comprehensive evaluation study, in a narrow sense, standards as specific references for evaluating computer ECG programs. The evaluation methodology used within the CSE project is described as a basis for presentation of results which are published elsewhere in this issue.
Keywords: Computerized Electrocardiography; Software Evaluation; Computer-Aided Diagnosis; Reference Standards; Diagnostic Efficacy